2023
DOI: 10.1002/adhm.202300951
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro and Ex Vivo Analysis of the Potential of GelMA Hydrogels as a Therapeutic Platform for Preclinical Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is a devastating condition with no curative therapy currently available. Immunomodulation can be applied as a therapeutic strategy to drive alternative immune cell activation and promote a proregenerative injury microenvironment. Locally injected hydrogels carrying immunotherapeutic cargo directly to injured tissue offer an encouraging treatment approach from an immunopharmacological perspective. Gelatin methacrylate (GelMA) hydrogels are promising in this regard, however, detailed ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…Transgenic D. rerio expressing GFP in neutrophils were imaged, with neutrophils exhibiting surveillant behaviour within the tail fin (figure 4c,d). Next, we cultured BV2 microglia, a widely used mouse cerebellar microglial cell line [24][25][26][27], and performed imaging at physiological temperature, 37°C, for 30 min (figure 4e). Microglia at this temperature exhibit typical ramified morphology and localized surveillant motions.…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic D. rerio expressing GFP in neutrophils were imaged, with neutrophils exhibiting surveillant behaviour within the tail fin (figure 4c,d). Next, we cultured BV2 microglia, a widely used mouse cerebellar microglial cell line [24][25][26][27], and performed imaging at physiological temperature, 37°C, for 30 min (figure 4e). Microglia at this temperature exhibit typical ramified morphology and localized surveillant motions.…”
Section: Resultsmentioning
confidence: 99%
“…After UV irradiation in the presence of LAP, it can be polymerized through free radical reaction, and effectively preserve drug factors and extend the half-life of drug release. In view of the advantages of GelMA such as plasticity, biocompatibility and biodegradability 46 , we prepared the Exos hydrogel sustained-release system and conducted a series of characterization. We found that it has good biocompatibility and simulates the mechanical properties of natural spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were then frozen at −80 °C, lyophilized, and the dry weight (Wdry) was recorded. The swelling ratio was calculated as Wwet/Wdry [ 10 ].…”
Section: Methodsmentioning
confidence: 99%